TEMATIZAÇÃO JORNALÍSTICA DA REFORMA POLÍTICA E PROJETO ELEIÇÕES LIMPAS: AGENDAMENTO (EDITORIAL) DE MOVIMENTOS SOCIAIS NA WEB - Oliveira, Thaís Helena Ferreira Neto (2016)
The research analyzes the journalistic thematization of political reform and Clean Elections Project, proposed by to Combat Electoral Corruption Movement (MCCE) in digital spaces, a study in five sites accompanying social movements, namely, Adital,Brasil de Fato, Fórum Nacional de Democratização da Comunicação, Pulsar Brasil e Revista Fórum. From journalistic features work analyzes the theming in the period from September to November 2014 and March to May 2015, with interface to the Theory of Agenda and scheduling in complex societies, addressing concepts of 'Science of Newspapers' journalism as a forum for discussion, civil society, public opinion formation, expression of social movements networking and media coverage of politics.